Synthesis of high voltage cathode materials for aqueous Al-ion battery - Fatin Umirah Jumadi (Nanyang Technological University, 2021)
The opportunity of exploring aluminium-ion batteries (AIBs) has surfaced in anticipation of future societal demand for high energy density and affordable batteries. AIBs are exceptionally attractive as aluminium is envisioned to provide a low-cost energy storage platform, due to its abundance in Earth’s crust. Additionally, the high volumetric capacity of aluminium (8046 mAh cm-3) [1] which is four to seven times larger than Lithium and Sodium, undoubtedly has the potential to drive the energy density of AIBs further on a per unit volume. Moreover, the potential safety hazard is reduced as Aluminium has better air stability as compared to Lithium. However aqueous systems of AIBs have exhibited fatal drawbacks [2]. Thus this provides a new prospect to discover a new synthesis of cathodic material to further optimize the cell efficiency of AIBs. This report investigates new and uncommercialized cathodic materials – Manganese Oxide (MnO2) through characterization techniques as well as evaluating coin cells at discharge rates with Ionic-Liquid Aluminium (ILA) as the anode.